Optimalisasi Tegangan Tabung (KvP) Terhadap Kejelasan Informasi Anatomi Dan Dosis Radiasi Pada Pemeriksaan CT Scan Kepala Area Basis Cranii - Agustina Dwi Prastanti; Yeti Kartikasari; Robets Pribadi; Andrey Nino Kurniawan; Dwi Rochmayanti (Jurnal Imejing Diagnostik (JImeD), 2022)
Background: Tube voltage (kVp) is one of the exposure factors on a head CT scan that can be varied to achieve a minimal radiation dose. Radiology installation of Bhakti Wira Tamtama hospital has a new CT scan modality that never variation its tube voltage. The variation of tube voltage is 80 kVp, 100 kVp, and 120 kVp. The aim of this research is to know and to analyse the most optimize tube voltage which can produce the best anatomy clarity and has the lowest radiation dose on a head CT scan examination of the base skull area that dominates CT scan examination.Methods: This research is descriptive analytic research conducted with an experimental approach. The study was conducted by varying the tube voltage to be used for head CT scan examination. There are 3 variations of tube voltage 80 kVp, 100 kVp, and 120 kVp where one variation contains 16 images for analyzing the clear anatomy of the base skull area. Then assessed by radiologists as the respondent. Data was analyzed by scoring where score 1 is not clear, score 2 is clear and score 3 is very clear. Radiation dose was obtained from CTDI and DLP records.Results: The results showed that there is no difference in anatomy clarity between variation of three tube voltage with p value 0,135. The anatomical clarity assessed includes anterior skull base, central skull base (fossa cranial middle, sphenoid, temporal bone, petrosous ridge), anterior clinoid processes, posterior margin of the lesser sphenoid wings, anterior and superior rim of the greater sphenoid wings, mastoid, and posterior skull base. All of them is very clear at 100 kVp and 120 kVp with value 100%. But at 80 kVp assessed clear at anterior and posterior skull base. So the value of anatomy clarity at 80 kVp is very clear only 71%. The effect of the difference in tube voltage on the radiation dose on a head CT scan of the base skull area showed a difference in the decrease in radiation dose from 120 kVp to 100 kVp for CTDI 39.9% and DLP 40.19%. There was a decrease in radiation dose from 100 kVp to 80 kVp for CTDI 52% and DLP 49.88%.Conclusion: The tube voltage setting on head CT scan examination of the base skull area can be applied with 100 kVp because this is evidenced by the same total score at 100 kVp and 120 kVp, which is 100% is very clear, while at 80 kVp tube voltage only 71% is very clear. And the radiation dose at 100 kVp is lower than 120 kVp.